Attraction Factors to Borneo Cultures Museum - Florence Shandie, David; Shaik Azahar, Shaik Hussain
The purpose of this study is to find out the attraction factors to the Borneo Cultures Museum. The museum is a historical place that is perfect for visiting on weekends and holidays. The researcher focused on three research objectives which are to identify the factors that cause visitors to be satisfied with the information on the exhibition panel, to study the measu res to attract the interest of visitors to the museum and to analyse the importance of museum institutions to visitors. The methodology used by the researcher is a quantitative method. In conclusion, the attraction factor needs to be improved and taken seriously so that the museum institution continues to move forward. The implication is that this study is very useful as a reference by museum management, future researchers, and the public.